Municipal water reuse for urban agriculture in Namibia: Modeling nutrient and salt flows as impacted by sanitation user behavior. (15th March 2016) - Woltersdorf, L.; Scheidegger, R.; Liehr, S.; Döll, P.
Abstract: Adequate sanitation, wastewater treatment and irrigation infrastructure often lacks in urban areas of developing countries. While treated, nutrient-rich reuse water is a precious resource for crop production in dry regions, excessive salinity might harm the crops. The aim of this study was to quantify, from a system perspective, the nutrient and salt flows a new infrastructure connecting water supply, sanitation, wastewater treatment and nutrient-rich water reuse for the irrigation of agriculture, from a system perspective. For this, we developed and applied a quantitative assessment method to understand the benefits and to support the management of the new water infrastructure in an urban area in semi-arid Namibia. The nutrient and salt flows, as affected by sanitation user behavior, were quantified by mathematical material flow analysis that accounts for the low availability of suitable and certain data in developing countries, by including data ranges and by assessing the effects of different assumptions in cases. Also the nutrient and leaching requirements of a crop scheme were calculated. We found that, with ideal sanitation use, 100% of nutrients and salts are reclaimed and the slightly saline reuse water is sufficient to fertigate 10 m 2 /cap/yr (90% uncertainty interval 7–12 m 2 /cap/yr). However, only 50% of the P contained in human excreta could be finally used for crop nutrition. During the pilot phase fewer sanitation users than expected used slightly more water per capita, used the toilets less frequently and practiced open defecation more frequently. Therefore, it was only possible to reclaim about 85% of nutrients from human excreta, the reuse water was non-saline and contained less nutrient so that the P was the limiting factor for crop fertigation. To reclaim all nutrients from human excreta and fertigate a larger agricultural area, sanitation user behavior needs to be improved. The results and the methodology of this study can be generalized and used worldwide in other semi-arid regions requiring irrigation for agriculture as well as urban areas in developing countries with inadequate sanitation infrastructure. Highlights: Our quantitative assessment supports the design/operation of water reuse infrastructures. The nutrient ratio (N, P, K, Ca, Mg) in wastewater differs from that required by crops. Little reuse water and P, while too much N, K, Ca and Mg are available for crops. Reuse water is generated to fertigate crops on 10 m 2 /cap (7–12 m 2 /cap) per year. 50% of P from human excreta is finally reused by crops.